Ruination - Reynolds, Anthony (Science fiction author) (League of legends., 2022)
"Camavor is a brutal land with a bloody legacy. Where the empire's knights go, slaughter follows. Kalista seeks to change that. When her young and narcissistic uncle, Viego, becomes king, she vows to temper his destructive instincts, as his loyal confidant, advisor, and military general. But her plans are thwarted when an assassin's poisoned blade strikes Viego's wife Isolde, afflicting her with a malady for which there is no cure. As Isolde's condition worsens, Viego descends into madness and grief, threatening to drag Camavor down with him. Kalista makes a desperate gambit to save the kingdom: She searches for the long-lost Blessed Isles, rumored to hold the queen's salvation if only Kalista can find them. But corruption grows in the Blessed Isles' capital, where a vengeful warden seeks to ensnare Kalista in his cruel machinations. She will be forced to choose between her loyalty to Viego and doing what she knows is right -- for even in the face of utter darkness, one noble act can shine a light that saves the world"--Book jacket.